TFPI2 Promotes Perivascular Migration in an Angiotropism Model of Melanoma - Mo, Jing; Zhao, Xiulan; Wang, Wei; Zhao, Nan; Dong, Xueyi; Zhang, Yanhui; Cheng, Runfen; Sun, Baocun (Frontiers in Oncology, 2021)
Purpose: Angiotropism is the process by which cancer cells attach to and migrate along blood vessels to acquire vasculature, disseminate and metastasize. However, the molecular basis for such vessel–tumour interactions has not been fully elucidated, partly due to limited experimental models. In this study, we aimed to observe and explore the molecular mechanism underlying angiotropism in melanoma. Methods: To monitor the interactions of human melanoma cells with the vasculature in vivo, a murine coxenograft model was employed by co-injecting highly and poorly invasive melanoma cells subcutaneously. To identify key pathways and genes involved in the angiotropic phenotype of melanoma, analysis of differentially expressed genes (DEGs) and gene set enrichment analysis (GSEA) were performed. The role of tissue factor pathway inhibitor 2 (TFPI2) in angiotropism was evaluated by immunostaining, adhesion assays, shRNA, and in vivo tumorigenicity. Angiotropism and TFPI2 expression were examined in surgical specimens of melanoma by immunohistochemical staining. Data from The Cancer Genome Atlas (TCGA) were analysed to explore the expression and prognostic implications of TFPI2 in uveal and cutaneous melanoma. Results: Highly invasive melanoma cells spread along the branches of intratumor blood vessels to the leading edge of invasion in the coxenograft model, resembling angiotropic migration. Mechanisms underlying angiotropism were primarily associated with molecular function regulators, regulation of cell population proliferation, developmental processes, cell differentiation, responses to cytokines and cell motility/locomotion. TFPI2 downregulation weakened the perivascular migration of highly invasive melanoma cells. High levels of TFPI2 were correlated with worse and better survival in uveal and cutaneous melanoma, respectively. Conclusion: These results provide a straightforward in vivo model for the observation of angiotropism and suggest that TFPI2 could inhibit the angiotropic phenotype of melanoma.